Study while you sleep: using targeted memory reactivation as an independent research project for undergraduates - Mar’i, Joud; Zhang, Robert; Mircic, Stanislav; Serbe-Kamp, Étienne; Meier, Matthias; Leonhardt, Aljoscha; Drews, Michael; Del Grosso, Nicholas A.; Antony, James W.; Norman, Kenneth A.; Marzullo, Timothy C.; Gage, Gregory J. (Advances in physiology education, 2025)
Why study when you could just sleep? We demonstrate how students can perform scalable research investigations to manipulate memory processing during sleep. It is a hands-on way to advance students’ understanding of sleep-based memory consolidation and the corresponding neural mechanisms using open-source software and do-it-yourself EEG tools. Newly acquired information is stabilized into long-term memory through the process of consolidation. Memories are not static; rather, they are constantly updated via reactivation, and this reactivation occurs preferentially during slow-wave sleep (SWS; also referred to as N3 in humans). Here we present a scalable neuroscience research investigation of memory reactivation using low-cost electroencephalogram (EEG) recording hardware and open-source software for students and educators across the K-12 and higher education spectrum. The investigation uses a method called targeted memory reactivation (TMR), whereby auditory cues that were previously associated with learning are represented during sleep, triggering the recall of stored memories and (through this) strengthening these memories. We demonstrated the efficacy of this technique on seven healthy human subjects (19–35 years old, 3 females, four males). The subjects learned to play a spatial memory game on an app where they associated pictures (e.g., a clock) with locations on a grid while they listened to picture-appropriate sounds (e.g., “tic-toc”); next, they took a nap while undergoing EEG recordings. During SWS, half of the sounds from the game were replayed by the app, while half were substituted with nonlearned sounds. Subjects then played the memory game again after waking. Results showed that spatial recall was improved more for cued than uncued memories, demonstrating the benefits of memory replay during sleep and suggesting that one may intervene in this process to boost recall of specific memories. This research investigation takes advantage of the importance of sleep for memory consolidation and demonstrates improved memory performance by cueing sounds during SWS. NEW & NOTEWORTHY Why study when you could just sleep? We demonstrate how students can perform scalable research investigations to manipulate memory processing during sleep. It is a hands-on way to advance students’ understanding of sleep-based memory consolidation and the corresponding neural mechanisms using open-source software and do-it-yourself EEG tools.